How EFL teachers perceive and self-evaluate the knowledge components in forming Technological Pedagogical Content Knowledge (TPACK) - Leimin Shi; Lili Jiang (English Language Teaching Educational Journal, 2022)
Technology is widely involved across the learning environment including its integration into teaching English as a foreign language (EFL); however, few studies have explored EFL teachers’ perceptions of technological pedagogical content knowledge (TPACK). This study investigates how EFL teachers perceive and self-evaluate knowledge of content (CK), pedagogy (PK), and technology (TK), the interplay of these with each other (TPACK), and the underlying influential factors for TPACK construction. The data were gathered in China from an online survey (n = 64) comprising 35 items on the TPACK components, and self-evaluation by nine survey participants of their TPACK in follow-up interviews. WeChat, the most popular social media App in China, was utilised as the data collection tool. The survey reveals teachers’ strong beliefs in the value of PK, CK and PCK and their positive beliefs about technological applications in EFL instruction. Consistent with these results, interviewees’ self-evaluation of TPACK demonstrates that they felt a high level of confidence in CK, PK and PCK but relatively less confidence when technology was integrated despite commonly applying technology to instruction. Influential factors include: 1) contextual factors; 2) knowledge of students; 3) demographic background; and 4) availability of quality training. Decision-makers’ financial support and policy-making, technological training in the integration of CK and/or PK, and a collaborative learning strategy are recommended.